(untitled) (Faridpur Medical College Journal, 2016)
Post-surgical wou infection is a crucial factor in surgical practice. Prolong use of postoperative antibiotic is common practice in our surgical world. This causes financial burden to our patients a antibiotic resistance. But international journals a literatures suggest using antibiotics as prophylaxis only at the time of operation a no further postoperative antibiotic is needed in clean contaminated surgery. This comparative cross-sectional study was done at the department of surgery, Sylhet MAG Osmani Medical College Hospital from 1st July 2007 to 30th June 2008. A total number of 100 patients of clean-contaminated elective laparotomy were selected. Patients were ra omly divided into two groups, in Group-I (got single dose preoperative Inj. Ceftriaxone) a in group-II (got single dose preoperative Inj. Ceftriaxone followed by Inj. Ceftriaxone for 2 days a then Cap. Cefxime for next 5 days). There is no statistically significant difference in outcome between two groups. So, single dose preoperative Inj. Ceftriaxone (1gm) is sufficient as a prophylaxis of surgical site infection in clean-contaminated elective surgery. Faridpur Med. Coll. J. Jan 2016;11(1): 6-10